Odpowiedź :
A) x^2 + 5x - 5x -25 = x^2 - 25
B) 100 - 100x + 10x - x^2 = 100 - 90x - x^2
C) a^2 + 1/4ab - 1/4ab - 1/16b^2 = a^2 - 1/16b^2
B) 100 - 100x + 10x - x^2 = 100 - 90x - x^2
C) a^2 + 1/4ab - 1/4ab - 1/16b^2 = a^2 - 1/16b^2
[tex]a) \ (x-5)(x+5) = x^{2}-5^{2} = x^{2}-25\\\\b) \ (10+x)(10-x) = 10^{2}-x^{2} = 100-x^{2}\\\\c) \ (a-\frac{1}{4}b)(a + \frac{1}{4}b) = a^{2} -(\frac{1}{4}b)^{2} = a^{2} -\frac{1}{16}b^{2}[/tex]
Wyjaśnienie
Wykorzystano wzór skróconego mnożenia:
(a + b)(a - b) = a² - b²